2004
DOI: 10.1093/eurpub/14.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patient delay among tuberculosis cases in Spain

Abstract: Although there is a universally enjoyed right to health care in Spain, some groups of TB patients could nevertheless be experiencing problems in seeking medical attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 8 publications
5
21
0
6
Order By: Relevance
“…Care seeking or patient delay is widely variable in literature, ranging from 4.9 to 162 days 18 . In our study, patient delay was similar to that found by other authors in India 19,20 , Japan 21 , Hong Kong 22 , and Spain 23 .…”
Section: Discussionsupporting
confidence: 91%
“…Care seeking or patient delay is widely variable in literature, ranging from 4.9 to 162 days 18 . In our study, patient delay was similar to that found by other authors in India 19,20 , Japan 21 , Hong Kong 22 , and Spain 23 .…”
Section: Discussionsupporting
confidence: 91%
“…, patients under these conditions are susceptible to TB (2,5,6). TB in such patients is characterized by increasing extrapulmonary involvement and miliary spread (2,3,(6)(7)(8).…”
Section: After a Steady Decline In The Incidence Of Tuberculosis (Tb)mentioning
confidence: 99%
“…TB in such patients is characterized by increasing extrapulmonary involvement and miliary spread (2,3,(6)(7)(8). The term miliary TB, first used to describe resemblance of the pathologic lesions to millet seeds, is now used for all forms of progressive disseminated hematogenous TB regardless of the pathologic picture.…”
Section: After a Steady Decline In The Incidence Of Tuberculosis (Tb)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that delays in tuberculosis diagnosis were associated with greater transmission of infection to contacts (9). Delays in the diagnosis and treatment of tuberculosis patients have been commonly reported in both developing and developed countries (10)(11)(12)(13)(14)(15)(16)(17)(18). The current study aimed to discuss the length of delays and possible reasons for delays in pulmonary tuberculosis patients.…”
mentioning
confidence: 99%